Advanced Textiles and Its Application in Food Preservation (Journal of Fiber Bioengineering and Informatics, 2024)
In today’s fast-paced life, ensuring food’s freshness, safety, and optimal nutritional and economic valueis paramount for both consumers and businesses. Textiles have played a significant role in the foodpreservation industry throughout history. With the continuous development of the textile and preservationindustries, novel methods have been explored to enhance the effectiveness of preservation. This articleprovides a comprehensive overview of textiles’ performance requirements and limitations in the foodpreservation process. Additionally, it introduces innovative techniques and recent advancements intextile materials designed explicitly for preservation purposes. Furthermore, the paper highlights thekey challenges that must be addressed in future research. Consequently, this scientific review servesas a valuable reference for the application and advancement of textiles in the dynamic field of foodpreservation.
Keywords: Textiles; Food Preservation; Intelligent Textile; Antimicrobial Textile.